Proton decay in general SU(S) models - Gómez, M. E. (HNPS Advances in Nuclear Physics, 2020)
We discuss proton decay induced by dimension-5 operators in supersymmetric models containing extra hypercharge-1/3 colour-triplets. We derive a general formula relating dimension-5 operator to the colour-triplet mass matrix. We show that certain zeros in the triplet mass-matrix together with some triplet coupling selection rules can lead to elimination of dimension-5 operators. We apply this mechanism to SU(5) and flipped 517(5) theories with extended Higgs sectors.